Microenvironment Effects on the Kinetics of the Alkaline Hydrolysis of Bispyridinium Conformers. Issue 11 (21st September 2013) - Vanzin, Douglas; Fiori, Simone; França Biondo, Polyana B.; Feltrim, Gisele; Gracetto, Augusto C.; Tessaro, André L.; Politi, Mario José; Caetano, Wilker; Hioka, Noboru
ABSTRACT The alkaline hydrolysis of a series of homologous reactants constituted by two reactive centers bridged by a methylene spacers chain, the 1, n‐bis(2‐azidepyridinium)alkanes (n = 3, 4, 5, 6, and 8), is investigated. The reaction under pseudo–first‐order condition was followed by ultraviolet–visible spectrophotometry. The presence of clear isosbestic point suggests the absence of stable intermediates. However, the intermediates 1‐(2‐azidepyridinium), n‐(2‐pyridone)alkanes (monocationic compounds), were isolated and characterized as well the reaction end products 1, n‐(2‐pyridone)alkanes (noncharged compounds). The kinetic analysis fitted to a two‐step consecutive reaction, where the k1/k2 values demonstrate the larger reactivity of the first step over the second one, especially for shorter bridged reactants. The OH− reaction order is one for each step. Although Debye–Hückel law was obeyed, the experimental point at ionic strength zero is much higher than the extrapolated one. In addition, the k1 values substantially decrease as KCl is added especially for shorter homologous whereas the effect on k2 is almost negligible. Simple charge density effects as a function of the spacer's length do not explain the observations. On the other hand, from the pronounced anion selectivity inhibition effects on k1 for the shorter derivatives, the existence of an equilibrium involving a conformer, a "sandwich‐type" complex with the OH− between the two pyridinium rings, with an "open‐stretched" conformer is proposed. For short‐bridged reactants, the complex conformer prevails whereas for long‐bridged compounds the stretched structure prevails. The results in acetonitrile/water seem to reflect changes in the equilibrium. The reaction is controlled by the balance between enthalpy and entropy. The contribution of the activation entropy in a short‐bridged reactant is higher than the long‐bridged one, which suggests an activated complex with high structural organization in the first reactants.